Bismuth tri-iodide-polystyrene composite for X-rays switching applications at room temperature. (September 2021) - Chaudhari, Ritu; Garg, Alka; Singh, Kulvinder; Tomar, Monika; Gupta, Vinay; RaviKant, Chhaya
Abstract: Bismuth tri-iodide is potential low toxic material for fabrication of room-temperature X-rays detector due to its relatively high atomic number and density. However, on increasing the thickness of detector, higher leakage current at low bias voltage and low mechanical strength are major issues in utilizing its full potential in radiation detection and in other practical applications. BiI3 -polystyrene composite pellets was prepared to get unique defects tolerance nature of material that improves signal/noise ratio. BiI3 -polystyrene composite was prepared by low-cost dry-tumble mixing technique. XRD observations gives information of preferred orientated planes perpendicular to c-axis and morphology study by SEM also confirms the same orientation. X-rays switching response recorded at different voltages (13–100 V) for detector performance measurements. Resistivity of BiI3 (10 7 ohm-cm) is less as compared to polystyrene (10 15 ohm-cm), it acts as conductive-tips in polystyrene-matrix and improves charge transfer to electrodes. These superior charge transfer properties lead to high photocurrent on-off ratio to 70 and suppress leakage current. Highlights: Bismuth tri-iodide is a good alternate of lead due to relatively low toxicity. First time soft (30Kvp) X-rays switching response for bulk polymer composite detector record at 13 V biased voltage. The response time for bulk detector towards X-Rays is 0.35 s. Polymer composite improves mechanical strength and crystallinity of detector without any nano-encapsulation. Signal to noise ratio for polymer composite is recorded upto 70.